2019
DOI: 10.1038/s41467-018-07829-z
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 binding to the PHD1 domain of histone demethylase KDM5A enables active site remodeling

Abstract: Histone demethylase KDM5A removes methyl marks from lysine 4 of histone H3 and is often overexpressed in cancer. The in vitro demethylase activity of KDM5A is allosterically enhanced by binding of its product, unmodified H3 peptides, to its PHD1 reader domain. However, the molecular basis of this allosteric enhancement is unclear. Here we show that saturation of the PHD1 domain by the H3 N-terminal tail peptides stabilizes binding of the substrate to the catalytic domain and improves the catalytic efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 69 publications
4
67
0
Order By: Relevance
“…The observed difference in K M app also explains the preference of KDM5 enzymes toward longer peptide substrates. 3,4 Acetylation of K14 and K18 is associated with active transcription, and a previous study identified a positive crosstalk between these modifications and K4me3. 8 Hence, we proceeded to test how acetylation of K14 (K14ac) and K18 (K18ac) affects KDM5A substrate engagement and activity.…”
Section: Kdm5a Recognizes An H3 Epitope Distal To K4mentioning
confidence: 92%
See 1 more Smart Citation
“…The observed difference in K M app also explains the preference of KDM5 enzymes toward longer peptide substrates. 3,4 Acetylation of K14 and K18 is associated with active transcription, and a previous study identified a positive crosstalk between these modifications and K4me3. 8 Hence, we proceeded to test how acetylation of K14 (K14ac) and K18 (K18ac) affects KDM5A substrate engagement and activity.…”
Section: Kdm5a Recognizes An H3 Epitope Distal To K4mentioning
confidence: 92%
“…5 While PHD1 is required for efficient demethylation in cells, the deletion of the PHD2 and PHD3 domains does not abrogate demethylase activity, and a KDM5A construct that lacks these domains (KDM5A 1-797 ) has been utilized for the in vitro characterization of this protein (Figure 1b). 3,4,6,7 The presence of multiple methylated lysine residues in the H3 tail ( Figure 1c) raises questions about the molecular basis for H3K4-specific demethylation by KDM5A. [8][9][10][11] Currently, there is limited information regarding the molecular details of KDM5A substrate recognition.…”
mentioning
confidence: 99%
“…3 E, right) [ 131 ]. Interestingly, the PHD1 domains of KDM5A and KDM5B have been shown to allosterically activate these enzymes upon binding their own product, H3K4me0 [ [132] , [133] , [134] ]. This positive feedback mechanism may drive propagation of demethylation along nucleosomes to remove large H3K4me3 domains upon switching to a transcriptionally inactive state, or serve to maintain methylation-free chromatin domains [ 131 , 135 ].…”
Section: Regulating H3k4me3 At Cpg Island-associated Gene Promotersmentioning
confidence: 99%
“…PHD3 is also known to form a fusion with NUP98 in acute leukemia 16 . We have previously shown that the PHD1 domain preferentially binds unmodified H3 42 and that the engagement of the PHD1 domain with its ligand allosterically enhances the demethylation activity of KDM5A by stabilizing substrate binding to the catalytic domain 43 . Despite the importance of PHD1 in the demethylase activity of KDM5A, there is limited structural information on how its PHD1 domain interacts with H3 and how it can discriminate against the methylation states of H3K4 peptides.…”
Section: Introductionmentioning
confidence: 99%